2019
DOI: 10.1038/s41589-018-0195-0
|View full text |Cite
|
Sign up to set email alerts
|

A chemical–genetic screen identifies ABHD12 as an oxidized-phosphatidylserine lipase

Abstract: Reactive oxygen species (ROS) are transient, highly reactive intermediates or byproducts produced during oxygen metabolism. However, when innate mechanisms are unable to cope with sequestration of surplus ROS, it causes oxidative stress, where excess ROS damage biomolecules. Oxidized phosphatidylserine (PS), a pro-apoptotic “eat me” signal, is produced in response to elevated ROS, yet, little is known of its chemical composition and metabolism. Here, we report a small molecule that generates ROS in different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(129 citation statements)
references
References 59 publications
7
113
0
Order By: Relevance
“…Indeed, the higher the number of bis‐allylic hydrogen atoms in a given acyl chain, the more likely it is to be oxidizable, and the rate of lipid peroxidation scales with the degree of unsaturation in membrane phospholipids (Figure A). While less energetically favorable, monounsaturated fatty acyl chains can also be oxidized in response to small molecule ROS inducers and physiological stimuli (e.g., see ref …”
Section: Lipid Peroxide Formation and Propagationmentioning
confidence: 99%
“…Indeed, the higher the number of bis‐allylic hydrogen atoms in a given acyl chain, the more likely it is to be oxidizable, and the rate of lipid peroxidation scales with the degree of unsaturation in membrane phospholipids (Figure A). While less energetically favorable, monounsaturated fatty acyl chains can also be oxidized in response to small molecule ROS inducers and physiological stimuli (e.g., see ref …”
Section: Lipid Peroxide Formation and Propagationmentioning
confidence: 99%
“…Similarly, pharmacological inhibition of ABHD12 resulted in a significant accumulation of LysoPS in human macrophages and a significant enhancement of the immune responses of the cells in vivo [17]. Importantly, Kelkar et al later showed that ABHD12 also catalyzed the hydrolysis of an oxidized-PS to LysoPS which was further hydrolyzed and degraded by ABHD12 [32]. More recently, LysoPS with a very-long-chain fatty acid (~C24:0), which is a preferential substrate for ABHD12, was shown to efficiently induce pro-inflammatory responses of macrophages via Toll-like receptor 2 (TLR2) [15].…”
Section: Abhd16a and Abhd12mentioning
confidence: 99%
“…All mammalian cell lines (HEK293T, HeLa, A549, THP1 and MCF7) described in this paper were purchased from ATCC, and cultured in complete medium [RPMI1640 supplemented with 10% (v/v) FBS, and 1% (v/v) penicillin-streptomycin (Pen-Strep) (MP Biomedicals)] at 37 °C with 5 % (v/v) CO 2 unless otherwise mentioned. The cell cultures were stained routinely with 4',6-diamidino-2-phenylindole (DAPI) and assessed by microscopy to ensure that they were devoid of any mycoplasma contamination using established protocols 33 . All cell lines were cultured in 15 cm tissue culture dishes (Eppendorf), and upon 80% confluence were harvested by scrapping, washed with Dulbecco's phosphate buffer saline (DPBS) (3x times), centrifuged at 200g for 5 mins to remove excess DPBS, and stored at -80 °C till further use.…”
Section: Mammalian Cell Culturementioning
confidence: 99%